2002
DOI: 10.1002/nbm.787
|View full text |Cite
|
Sign up to set email alerts
|

Applications of diffusion‐weighted and diffusion tensor MRI to white matter diseases – a review

Abstract: This paper reviews the current applications of diffusion-weighted and diffusion tensor MRI in diseases of the brain white matter. The contribution that diffusion-weighted imaging has made to our understanding of white matter diseases is critically appraised. The quantitative nature of diffusion MRI is one of its major attractions; however, this is offset by the more advanced hardware required to collect diffusion-weighted images reliably, and the more complex processing to produce quantitative parametric diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
261
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(266 citation statements)
references
References 41 publications
1
261
0
2
Order By: Relevance
“…However, if it were coupled with information on ECS and ICS volume fractions, new insights into axonal architecture can be gained such as an estimate of the axon count, an important parameter in determining function after spinal cord injury (Schwartz et al, 2005b) or quantification of axon loss, which would affect the ECS and ICS volume fractions, and demyelination, which would increase the displacement profile FWHM, both of which are hallmarks of spinal cord injury and a variety of WM diseases from multiple sclerosis to Alzheimer's disease (Budde et al, 2007;Horsfield and Jones, 2002). FWHM and zero-displacement probability have been observed to increase and decrease, respectively, in the presence of axon loss and demyelination (Assaf et al, 2002a), which we have also observed in ICS-weighted simulations of synthetic circular axons exhibiting only 10% axonal loss (data not shown).…”
Section: Discussion Estimating Mean Axon Diameter With Qsimentioning
confidence: 99%
See 1 more Smart Citation
“…However, if it were coupled with information on ECS and ICS volume fractions, new insights into axonal architecture can be gained such as an estimate of the axon count, an important parameter in determining function after spinal cord injury (Schwartz et al, 2005b) or quantification of axon loss, which would affect the ECS and ICS volume fractions, and demyelination, which would increase the displacement profile FWHM, both of which are hallmarks of spinal cord injury and a variety of WM diseases from multiple sclerosis to Alzheimer's disease (Budde et al, 2007;Horsfield and Jones, 2002). FWHM and zero-displacement probability have been observed to increase and decrease, respectively, in the presence of axon loss and demyelination (Assaf et al, 2002a), which we have also observed in ICS-weighted simulations of synthetic circular axons exhibiting only 10% axonal loss (data not shown).…”
Section: Discussion Estimating Mean Axon Diameter With Qsimentioning
confidence: 99%
“…Diffusion magnetic resonance imaging (MRI) techniques, primarily diffusion weighted imaging (DWI) and diffusion tensor imaging (DTI), provide a non-invasive means to provide indirectly, that is without explicitly resolving the structures, estimates of WM tract orientation and axon integrity (Horsfield and Jones, 2002;Le Bihan, 2003). The concept of diffusion MRI techniques is to measure the microscopic displacement from self-diffusion of molecules endogenous to WM, typically water.…”
Section: Introductionmentioning
confidence: 99%
“…These applications employ both the directional anisotropy that can be measured by DTI 4,5 as well as removal of this anisotropy through the use of the tensor trace. [6][7][8] For example, DTI is presently being explored as a research tool to study brain development, 9,10 multiple sclerosis, 11,12 amyotrophic lateral sclerosis (ALS), 13 stroke, 14,15, schizophrenia 16,17 and reading disability, 18 while trace imaging has become an essential part of clinical acute stroke assessment. [19][20][21][22] As first shown by Basser et al, 4 the diffusion ellipsoid obtained from DTI can not only provide a quantitative orientation-independent measure of diffusion anisotropy, 23,24 but also the predominant direction of water diffusion in image voxels.…”
Section: Introductionmentioning
confidence: 99%
“…DTI uses diffusion weighted measurements along at least six noncollinear directions to estimate a rank-two diffusion tensor at each point in the image, which is proportional to the covariance matrix of a 3D Gaussian distribution over molecular displacements. A scalar value commonly derived from the tensor is fractional anisotropy, a measure of dispersion in the tensor eigenvalues, which has been shown to be locally or globally reduced in a number of diseases [4], as well as some psychiatric disorders such as schizophrenia [5], reflecting changes in the underlying tissue. The principal eigenvector of the tensor, indicating the direction of greatest meansquared displacement, was the original basis for dMRI-based white matter fibre tracking, which has provided insights in basic neuroscience with regard to the connectivity of the brain (e.g.…”
Section: Introductionmentioning
confidence: 99%